2017
DOI: 10.15740/has/au/12.techsear(5)2017/1226-1232
|View full text |Cite
|
Sign up to set email alerts
|

Bio-physical characters of maize (Zea mays L.) genotypes to elevated carbon dioxide and temperature regimes

Abstract: SUMMARY :Higher atmospheric CO 2 concentration may influence positively plant production.Carbon dioxide was substrate for photosynthesis and gradient increase between the ambient air and mesophyll cells. Plants respond not only to change in surrounding CO 2 concentration, but to modifications of their microenvironment. Plants with C 4 photosynthetic pathway showed negligible photosynthetic response to elevated CO 2 because the C 4 cycle increased the CO 2 concentration in bundle sheath cells to the point where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…In the present study, we found that under eCO 2 concentrations, the fennel plants exhibited distinct growth responses, including increases in plant length, stem diameter, tiller number, and SPAD value. The results are consistent with the results of previous studies reporting that several plants, such as Zea mays, sugarcane, and Sorghum bicolor, exhibit improved growth responses in terms of leaf area, plant height, and total mass under high CO 2 conditions (De Souza et al, 2008;Sicher and Barnaby, 2012;Adishesha et al, 2017;Khanboluki et al, 2018;Huang et al, 2019;Mina et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, we found that under eCO 2 concentrations, the fennel plants exhibited distinct growth responses, including increases in plant length, stem diameter, tiller number, and SPAD value. The results are consistent with the results of previous studies reporting that several plants, such as Zea mays, sugarcane, and Sorghum bicolor, exhibit improved growth responses in terms of leaf area, plant height, and total mass under high CO 2 conditions (De Souza et al, 2008;Sicher and Barnaby, 2012;Adishesha et al, 2017;Khanboluki et al, 2018;Huang et al, 2019;Mina et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Leaf area index and chlrophyll content of leaves were also significantly impacted under the different treatments however, the cultivar treatment interaction was not significantly different at both the crop stages (Table 4a). Adishesha et al (2017) reported that the cholorophyll content of maize increased under elevated CO2 environment and reduced under the tropospheric O3 concentration (Bhatia et al, 2014). Deterioration in chlorophyll content of leaves under EO might be because of damage to the chloroplast due to change in membrane permeability (Zhu et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“… * Reference: 1 Mina et al [ 68 ]; 2 Adishesha et al [ 74 ]; 3 Sicher and Barnaby [ 75 ]; 4 Huang et al [ 62 ]; 5 Vu et al [ 12 ]; 6 Souza et al [ 13 ]; 7 Chaudhuri et al [ 76 ]; 8 Khanboluki et al [ 69 ]. The symbols mean an increase (↑) and no difference (=) in relation to control plants ([CO 2 ] ambient).…”
Section: Figurementioning
confidence: 99%